Design and Construction of an Automatic Coffee Drink Mixing Machine Based on Arduino - Lestari, Dini; Ashari, Runi; Nasution, Vikram Taufik; Bangun, Zuriah Rezky Br; Sembiring, David JM; Surbakti, Asprina Br (Karya Techno Solusindo, 2025)
The development of technological knowledge in Indonesia is growing very rapidly along with increasing technological knowledge such as automatic coffee drink mixers. This automatic coffee brewing system is defined as a system that is defined as a system that is able to make human work easier and shorten time. Therefore, we need a medium that controls via Arduino-based Android control, with the aim of making it easier to access information. This Arduino-based Android control system will make it easier to access automatic coffee drink mixers by setting the appropriate ingredient measurements needed. Through Android control, the process of making coffee drinks automatically becomes optimal and more effective in making coffee drinks. The system used in this automatic coffee drink mixer is via Android control which is carried out using the C programming language which is connected to the MIT invectore Bluetooth App. REFERENCES Ardiyanto, A., Ariman, & Supriyadi, E. (2021). ALAT PENGUKUR SUHU BERBASIS ARDUINO MENGGUNAKAN SENSOR INFRAMERAH DAN ALARM PENDETEKSI SUHU TUBUH DIATAS NORMAL. Sinusoida, 23(1). Arif Kurniawan. (2018). Rancang Bangun Alat Pembuat Minuman Kopi Otomatis Berbasis Mikrokontroler. UNIVERSITAS TEKNOLOGI YOGYAKARTA. Arifin, N. Y., Borman, R. I., Ahmad, I., Setyaning Tyas, S., Sulistiani, H., Hardiasnyah, A., & Suri, G. P. (2021). Analisa Perancangan Sistem Informasi (Pertama). Yayasan Cendikia Mulia Mandiri. Fahmizal, Mayub, A., Arrofiq, M., & Ruciyanti, F. (2021). Mudah Belajar Arduino dengan pendekatan berbasis Fritzing, Tinkercad dan Proteus. Deepublish. Fikri Alfaridzi, M., & Agustiawan. (2020). Rancang Bangun Mesin Pembuat Air Kopi Dengan Sistem Robotik. Seminar Nasional Industri Dan Teknologi (SNIT), 1, 328–368. Firmawati, N., Farokhi, G., & Wildian, W. (2019). Rancang Bangun Mesin Pembuat Minuman Kopi Otomatis Berbasis Arduino UNO dengan Kontrol Android. JITCE (Journal of Information Technology and Computer Engineering), 3(01), 25–29. https://doi.org/10.25077/jitce.3.01.25-29.2019 FURQAN, A. (2023). PERANCANGAN APLIKASI SIMULASI TES TOEFL BERBASIS ANDROID. UNIVERSITAS ISLAM NEGERI AR-RANIRY. Hamzanwadi, Fathurrahman, I., Wajdi, M. F., Universitas Hamzanwadi, Mandala Putra, H., Universitas Hamzanwadi, Widarina, B. V., & Universitas Hamzanwadi. (2022). Sistem Informasi Geografis Pemetaan Sebaran Data Covid-19 Pada Puskesmas Kerongkong Kabupaten Lombok Timur Berbasis WebImam. Infotek : Jurnal Informatika Dan Teknologi, 5(1), 42–52. https://doi.org/10.29408/jit.v5i1.4392 Hardiyansyah, M. V. (2021). Rancang Bangun Sistem Kontrol Suhu Pada Mesin Oven Kopi Tray Rotary Berbasis Arduino. Jurnal Crankshaft, 4(1), 67–76. https://doi.org/10.24176/crankshaft.v4i1.5915 Janna, N. M., Aisma, & Arsyam, M. (2021). Makanan Dan Minuman Dalam Islam. https://doi.org/10.31219/osf.io/49us8 Khakim, L. (2023). Buku Ajar Mikrokontroler Atmega328 (Moh. Nasrudin, Ed.). PT. Nasya Expanding Management. Laksono, D. T., Ulum, M., & Hakim, L. (2020). Rancang Bangun Pembuat Kopi Otomatis Berbasis Arduino Mega. Jurnal Teknik Elektro Dan Komputer TRIAC, 7(1), 50–97. Naim, M. (2021). BUKU AJAR SISTEM KONTROL DAN KELISTRIKAN MESIN (Moh. Nasrudin, Ed.). PT. Nasya Expanding Management. Pratama, R., Saputra, Z., & Silalahi, P. (2022). MESIN MINUMAN KOPI OTOMATIS BERBASIS IOT. Prosiding Seminar Nasional Inovasi Teknologi Terapan. Samania, N., Nirsal, & Fa’rifah, R. Y. (2020). RANCANG BANGUN APLIKASI E-VOTING PEMILIHAN KETUA UMUM HIMPUNAN MAHASISWA INFORMATIKA (HMTI) UNIVERSITAS COKROAMINOTO PALOPO BERBASIS WEBSITE. D’computare: Jurnal Ilmiah Teknologi Informasi Dan Ilmu Komputer, 10(1). https://doi.org/10.30605/dcomputare.v10i1.27 Suhartono, Hartanto, T. J., Hutahaean, S. DT., Nawir, M., & Dinata, P. A. C. (2023). Buku Ajar Fisika Berbasis Inkuiri: Materi Kajian Rangkaian Listrik Arus Searah. EUREKA MEDIA AKSARA. Suryanto, A., Maliki, M. I., & Universitas Bina Sarana Informatika. (2022). Penerapan Model Rapid Application Development (RAD) Dalam Rancang Bangun Sistem Informasi Warga. Infotek : Jurnal Informatika Dan Teknologi, 5(1), 197–208. https://doi.org/10.29408/jit.v5i1.4887 Triana, D. D., & Sarifah, I. (2023). Membangun Keunggulan Kompetitif Barista dalam Pelayanan Bisnis Kopi Melalui Pelatihan di BBPLK Bekasi.